Inside Back Cover: Azulenylcarbenes: Rearrangements on the C11H8 Potential Energy Surface (Chem. Eur. J. 35/2016). Issue 35 (4th July 2016) - Henkel, Stefan; Pollok, Corina H.; Schleif, Tim; Sander, Wolfram
Abstract : Four of the five possible isomers of azulenylcarbenes were synthesized, isolated in low temperature matrices, and spectroscopically characterized. While 1‐azulenylcarbene shows a slight preference for a singlet ground state, the other isomers have triplet ground states. The singlet—triplet splittings in azulenylcarbenes roughly parallel the π‐electron densities at the various positions in the azulene rings. More information can be found in the Full Paper by W. Sander et al. onpage 12479 ff.